2023
DOI: 10.1038/s41534-023-00756-y
|View full text |Cite
|
Sign up to set email alerts
|

Counterfactual communication without a trace in the transmission channel

Wei-Wei Pan,
Xiao Liu,
Xiao-Ye Xu
et al.

Abstract: We report an experimental realization of a modified counterfactual communication protocol that eliminates the dominant environmental trace left by photons passing through the transmission channel. Compared to Wheeler’s criterion for inferring past particle paths, as used in prior protocols, our trace criterion provides stronger support for the claim of the counterfactuality of the communication. We verify the lack of trace left by transmitted photons via tagging the propagation arms of an interferometric devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Salih's error in the analysis of his 'paradox' does not invalidate his interesting proposal for counterportation: a transfer of a quantum state in such a way that the carriers of the information are not present in the transmission channel in the sense that they do not leave a trace of the same order of magnitude as a localised carrier would leave, as it was achieved for a transfer of classical information, see [17]. However, it shows that the method holds only if the modification [11] is applied.…”
Section: Discussionmentioning
confidence: 99%
“…Salih's error in the analysis of his 'paradox' does not invalidate his interesting proposal for counterportation: a transfer of a quantum state in such a way that the carriers of the information are not present in the transmission channel in the sense that they do not leave a trace of the same order of magnitude as a localised carrier would leave, as it was achieved for a transfer of classical information, see [17]. However, it shows that the method holds only if the modification [11] is applied.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have revisited the area of counterfactual quantum communication and showed that a current of angular momentum L mod 2 z  which carries one bit of information can travel through the transmission channel, without the transmission of the particle itself [36]. This nature of counterfactual quantum theory has motivated researchers to delve deeper into the field, examining its fundamental principles [37], experimental validations [38][39][40], and potential applications in developing protocols without particle exchange [41,42]. Feasibility of implementation of digital signature [43] and certificate authorization [44] in counterfactual manner is established.…”
Section: Introductionmentioning
confidence: 99%
“…This scheme is unique and possesses certain benefits over the conventional methods of quantum teleportation or remote state preparation of entangled states, as here, the transmission channel does not require any quantum or classical particle to pass through it. The work is also inspired by the idea of combining two rapidly developing and interesting facets of quantum communication: (i) counterfactual quantum communication ( [40,43] and references therein) and (ii) quantum networks ( [45,46] and references therein). In view of the recent successful experimental realizations of counterfactual quantum communication [26,28,[38][39][40], and escalated interest in quantum networks to realize quantum internet for sensing, communication, and computing networks, such investigation of the feasibility of counterfactual quantum network becomes inevitable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation